2015
DOI: 10.4149/bll_2015_139
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of TREM-1 and TREM-2 expression in bronchoalveolar lavage fluid in sarcoidosis and other lung diseases

Abstract: BACKGROUND: Triggering receptors expressed on myelocytes (TREM) belong to new molecules with a great role in innate immune system and infl ammation. While TREM-1 is known for its pro-infl ammatory activity, the TREM-2 has anti-infl ammatory activity and has a great impact on granuloma formation, typical sign of sarcoidosis and other granulomatous diseases. METHODS: In our study, we compared the TREM-1 and TREM-2 receptor expressions on the myeloid cell surfaces in bronchoalveolar lavage fl uid in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Two recent studies have implicated the receptor as a pro-inflammatory mediator in airway inflammation. Analysis of BALF from patients with asthma showed increased expression of TREM-2 which was associated with increased eosinophil and eosinophilic inflammation 41 . Another study has shown that TREM-2 was upregulated in the lungs of an experimental model of melioidosis and TREM-2 deficient mice had markedly reduced inflammation 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies have implicated the receptor as a pro-inflammatory mediator in airway inflammation. Analysis of BALF from patients with asthma showed increased expression of TREM-2 which was associated with increased eosinophil and eosinophilic inflammation 41 . Another study has shown that TREM-2 was upregulated in the lungs of an experimental model of melioidosis and TREM-2 deficient mice had markedly reduced inflammation 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Genes increased with progressive Scadding staging were enriched for IL1, IL8 and IL6 pathways (Figure 2A), previously associated with inflammatory bowel disease [21] and lung fibrosis [18]. Interestingly, many of these genes are also increased with changes in clinical traits not included in the definition of Scadding stage, such as increased bronchial wall thickening (68 genes; TREM2, CHIT1, LGMN) and decreased FEV1% and FVC% (47 and 6 genes; IDI1 and INSIG1), previously reported in sarcoidosis [22, 23].…”
Section: Resultsmentioning
confidence: 63%
“…CD4 ve CD8 değerleri özellikle T lenfositlerin hakimiyetinin olduğu pek çok hastalıkta önem taşımaktadır (13)(14)(15). Mevcut çalışmamızda yeterli hasta sayısında BAL'ın yapılmamış, CD4 ve CD8 düzeylerinin incelenmemiş olması nedeniyle diğer parametrelerimizle birlikte değerlendirmeye alamadık.…”
Section: Discussionunclassified